Comparison of dose and time effects of flavonoids, alone or in combination, on the induction of mineralization markers in human osteoblast-like cells - Rabelo, Rafaela Laruzo [UNESP]; Nunes, Gabriel Pereira [UNESP]; Peres, Geórgia Rondó [UNESP]; Rios, Rafael Araújo [UNESP]; de Souza, Maria Eduarda [UNESP]; Braga, Gabriela Pacheco de Almeida [UNESP]; Duque, Cristiane [UNESP] (Elsevier, 2025)
OBJECTIVE: This study compared the cytotoxicity, alkaline phosphatase (ALP) activity, and mineralization-inducing effects of flavonoids on human osteoblast-like Saos-2 cells. DESIGN: Saos-2 cells were treated with quercetin, myricetin, pinocembrin, kaempferol, isoquercitrin (Iso), rutin (Rut), taxifolin (Tax), ampelopsin (Amp), epigallocatechin-3-gallate (EGCG), and chrysin at 100, 50, and 25 µM for 48 h. Metabolic activity, ALP activity and mineral deposition were assessed via resazurin, thymolphthalein and Alizarin Red S staining assays, respectively, after 8 and 14 days. Calcium hydroxide was used as positive control, and untreated cells (DMEM) as negative control. Based on initial screening, Tax, Iso, Rut and Amp were selected for double combination treatments (at 50/50 µM and at 25/25 µM), and the same assays were performed. Data were analyzed using ANOVA and Tukey's test (α = 0.05). RESULTS: Comparing the flavonoids, regardless of time and concentration, only chrysin at 100 µM and 50 µM significantly reduced cell viability. Iso, Rut, Tax, and Amp exhibited the highest ALP activity and mineralized nodules formation, significantly outperforming the other flavonoids and DMEM control, particularly at 50 and 25 µM (p < 0.05). Among the combinations, Tax+Iso, Tax+Amp and Tax+Rut, at 25/25 µM demonstrated higher ALP activity and enhanced mineral deposition compared to the other flavonoid combinations and DMEM (p < 0.05). CONCLUSIONS: Based on this preliminary in vitro model, Tax, Iso, Rut, and Amp, both individually and in combination, effectively promote biomineralization in Saos-2 cells, without inducing cytotoxic effects. These flavonoids hold significant potential for osteogenic applications, warranting further in vivo studies and clinical trials to optimize their therapeutic use.